RECYCLING AND UTILIZATION OF AVIATION ENGINEERING: THE GLOBAL TRENDS AND PECULIARITIES OF INTRODUCTION - Бойченко C. В.; Іванченко, О. В.; Яковлєва, А. В. (Science-based technologies, 2017)
This work is devoted to problems of disposal and recycling of out-of-date aircraft and their components. The features proper handling vehicles aviation industry, emerged from the operation were considered. The problem of air transport wastes in Ukraine and abroad was studied. The analysis of existing methods and technologies aimed at the rational and proper management of spent aircraft. The necessity of introduction of comprehensive utilization of aircraft was proved. We consider environmental and economic problems associated with the disposal and recycling of aviation vehicles, their components and assemblies. The experience of the utilization of aircraft leading airlines was studied. The significance and feasibility of introduction recycling programs in the field of waste management of the aviation industry at the state level have been proposed and reasonably.